EVALUATION OF THE COEFFICIENT OF TEMPERATURE CONDUCTIVITY OF SULFUR CONCRETE - Chakenov, B.K. (Recent Contributions to Physics, 2018)
The coefficient of temperature conductivity of sulfur concrete out of the phase transference zone has been evaluated through the well known decision of the heat conductivity equation for spherical body and through the profiles of temperature measured experimentally. A good agreement with calculation of the coefficient through the Ostrogradsky-Gauss theorem has been observed.